1981
DOI: 10.1364/ao.20.000440
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of single-mode optical fiber filters

Abstract: The fabrication of narrowband highly reflecting filters in single-mode step-index fibers was reported recently by Hill et al. [Appl. Phys. Lett. 32, 647 (1978)]. The underlying effect on which these filters are based is a photoinduced refractive-index change in the GeO(2) used as a core dopant in SiO(2) fibers. A study is reported aimed at the characterization of such optical fiber filters. A theoretical model is developed, and relevant fiber parameters are determined through intercomparison with experiment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(47 citation statements)
references
References 6 publications
0
46
0
1
Order By: Relevance
“…Lam et al [4] showed that photosensitivity at 488 nm is a two-photon absorption process, Following this, Meltz et al [5] suggested that germanosilicate glass should be highly photosensitive at the corresponding one-photon wavelength of 244nm. They externally exposed the side of a germanium-doped fibre to two interfering plane waves at 244 nm.…”
Section: Photosensitivity In Glassmentioning
confidence: 99%
“…Lam et al [4] showed that photosensitivity at 488 nm is a two-photon absorption process, Following this, Meltz et al [5] suggested that germanosilicate glass should be highly photosensitive at the corresponding one-photon wavelength of 244nm. They externally exposed the side of a germanium-doped fibre to two interfering plane waves at 244 nm.…”
Section: Photosensitivity In Glassmentioning
confidence: 99%
“…FBGs play an important role in spectral linewidth control of fiber lasers. The reflectivity of the uniform grating with constant modulation amplitude and constant period can be obtained using the coupled mode theory [10], given by the following formula: where R is the coefficient that determines the grating strength (R = 1 for strong grating and R = 0.5 for weak grating), Dn is the refractive index modulation, k B is the central wavelength of operation (Bragg wavelength), and N is the number of grating lines along the whole length of the grating.…”
Section: Polarization-independent Circulatormentioning
confidence: 99%
“…The grating reflectivity with constant amplitude modulation and period can be described as follow [4]:…”
mentioning
confidence: 99%